Free Movement, Open Borders and the Global Gains from Labor Mobility - Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
Straightforward economic arguments point to the potential for large global output gains from movement of labor from less to more productive locations. Yet the politics of receiving countries seems resistant, characterized rather by efforts to limit migration, or to stop it altogether. In this paper we examine the foundations of claims of large welfare gains through free mobility, studying implications of liberalizing migration for world welfare under a variety of models, paying attention not only to overall gains but also to how gains are distributed, and reviewing attempts to quantify the benefits. We conclude by asking how far considerations beyond economics motivate keenness to impose restrictions on migration.
Keywords: 330